Purchasing and supply chain management - Monczka, Robert M. (Thomson/South-Western, 2005)
Purchasing and Supply Chain Management, 3e is a turnkey solution for providing current and thorough coverage for this critical area of the supply chain. This book is not only a text but a reference as well and is now established as one of the leading-edge strategy and purchasing books. Students gain contextual insights and knowledge into the strategies, processes, and practices of purchasing through use of the many cases and examples. Because of their relationships with executives and practitioners worldwide, the authors are able to present unique and up-to-date insights that lead to greater understanding of the purchasing process. Purchasing and Supply Chain Management provides a hands-on, applied approach that has been thoroughly tested with student audiences to ensure learning success.